A hands-on introduction to forensic science cracking the case - Okuda, Mark M.; Stephenson, Frank H. (CRC Press, Taylor & Francis Group, 2015)
This book is to present a novel way of teaching forensic science and, more importantly, a different way of presenting any science discipline whether it be chemistry, physics, or biology.